Role of Hydrogen and Temperature in Hydrogen Embrittlement of Equimolar CoCrFeMnNi High-entropy Alloy - Lee, Junghoon; Park, Hanji; Kim, Myeonghyun; Kim, Han-Jin; Suh, Jin-yoo; Kang, Namhyun (KOREAN INST METALS MATERIALS, 2021)
We investigated the effects of hydrogen and temperature on hydrogen embrittlement (HE) of cold-rolled equimolar CoCrFeMnNi high-entropy alloy (HEA). The HE exhibited intergranular fracture in this HEA at 298 and 177 K. At 177 K, more twins formed than at 298 K, and this acted as a hydrogen-diffusion path. During deformation, local stress was concentrated at the triple junction consisting of grain and twin boundaries. Hydrogen diffused predominantly along the boundary and encountered stress-concentration regions. Cracks initiated and propagated predominantly through the grain/twin boundaries by hydrogen diffusion at 298 and 177 K. Therefore, HE occurred at 298 and 177 K. At 77 K, hydrogen was distributed throughout the specimen as twin formation was more active. The cryogenic temperature of 77 K caused the hydrogen to become trapped and thus not diffuse into the stress-concentration region. Thus, there was no significant HE at 77 K. Graphic abstract
Keywords: AUSTENITIC STAINLESS-STEELS; DIFFUSION-COEFFICIENT; INDUCED CRACKING; TENSILE; RESISTANCE; PRESTRAIN; BEHAVIOR; GRAIN; MN